2010
DOI: 10.1002/ibd.21264
|View full text |Cite
|
Sign up to set email alerts
|

4SC-101, a novel immunosuppressive drug, inhibits IL-17 and attenuates colitis in two murine models of inflammatory bowel disease†

Abstract: 4SC-101 is a novel immunosuppressive drug with excellent potential for the treatment of intestinal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 34 publications
3
57
0
Order By: Relevance
“…However, we showed previously that Vido inhibits IL-17 secretion by peripheral blood mononuclear cells (PBMCs) independently of its effects on cellular proliferation (Fitzpatrick et al, 2010a). Specifically, we found that the inhibitory effects of Vido on cellular proliferation could be reversed in the presence of exogenous uridine (Uri) (Fitzpatrick et al, 2010a). In contrast, Uri could not reverse the inhibitory effect of Vido on phytohemagglutinin-stimulated IL-17 secretion by PBMCs.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…However, we showed previously that Vido inhibits IL-17 secretion by peripheral blood mononuclear cells (PBMCs) independently of its effects on cellular proliferation (Fitzpatrick et al, 2010a). Specifically, we found that the inhibitory effects of Vido on cellular proliferation could be reversed in the presence of exogenous uridine (Uri) (Fitzpatrick et al, 2010a). In contrast, Uri could not reverse the inhibitory effect of Vido on phytohemagglutinin-stimulated IL-17 secretion by PBMCs.…”
Section: Introductionmentioning
confidence: 89%
“…Because of its capability to inhibit DHODH, Vido can inhibit leukocyte proliferation (Fitzpatrick et al, 2010a;Kulkarni et al, 2010). However, we showed previously that Vido inhibits IL-17 secretion by peripheral blood mononuclear cells (PBMCs) independently of its effects on cellular proliferation (Fitzpatrick et al, 2010a). Specifically, we found that the inhibitory effects of Vido on cellular proliferation could be reversed in the presence of exogenous uridine (Uri) (Fitzpatrick et al, 2010a).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although some studies have shown that antibody depletion of IL-17 increases the severity of acute colitis in mice (250), other mouse experiments conversely demonstrated that IL-17 receptor (IL-17R) deficiency reduces colitis severity (251). Novel drugs that block IL-17 activity have also been shown to confer protection in models of chronic colitis (252,253). Thus, there is currently much evidence to suggest a critical role for Th17 cells and their associated cytokines in UC pathogenesis.…”
Section: Ulcerative Colitis Pathophysiologymentioning
confidence: 99%